On the development of health insurance in low-income countries: the case of African countries - (:unkn) unknown (My University, 2008)
Health financing reforms in most low-income countries promote social and micro health insurance, in order to reduce direct spending by patients. Three phases of development can be distinguished in African countries: at first, schemes were developed only for the formal sector, then micro health insurance targeted the informal sector, and finally, health insurance was included in larger plans to reach universal coverage. The impact of health insurance is, as yet, difficult to assess. If beneficiaries have a better access to health services, the financing of health sector is not significantly improved, and there is no change in professional behaviour, in particular, in public facilities. In spite of their limits, social health insurance schemes continue to be implemented, but as a part of hybrid financing system, fitting with the abilities of low-income countries.
Keywords: African Research